2009
DOI: 10.1080/00016350802459264
|View full text |Cite
|
Sign up to set email alerts
|

Dental anxiety and alexithymia: Gender differences

Abstract: In a sample representing Finnish adult dental patients, alexithymia was associated with dental anxiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 34 publications
1
10
1
Order By: Relevance
“…Gender differences were found in the DIF factor of alexithymia, with female students showing higher scores, which contrasts with research that indicates that males have higher levels of alexithymia than females (Chen and Chung, 2016). Nevertheless, our finding is consistentwith other studies that show the converse (Levant et al, 2009; Viinikangas et al, 2009). The magnitude of the difference was small but indicates that females may have more difficulties in identifying their feelings.…”
Section: Discussionsupporting
confidence: 94%
“…Gender differences were found in the DIF factor of alexithymia, with female students showing higher scores, which contrasts with research that indicates that males have higher levels of alexithymia than females (Chen and Chung, 2016). Nevertheless, our finding is consistentwith other studies that show the converse (Levant et al, 2009; Viinikangas et al, 2009). The magnitude of the difference was small but indicates that females may have more difficulties in identifying their feelings.…”
Section: Discussionsupporting
confidence: 94%
“…Endogenous etiology is considered to be at least as important and it has been suggested that dental fear is part of a generalized anxiety syndrome involving multiple phobias and psychiatric diagnoses, such as depression and anxiety (12)(13)(14)(15). Dental fear is also associated with certain personality traits, for example alexithymia (15)(16)(17)(18)(19). This association between dental fear and psychological disorders has been suggested to represent individuals' endogenous vulnerability (15,20).…”
mentioning
confidence: 99%
“…The explanatory variable, dental fear, was measured using a validated and reliable questionnaire, the Modified Dental Anxiety Scale (MDAS) . The MDAS measures patient's dental fear with five questions considering a forthcoming dental visit, the dentist's waiting room, tooth drilling, tooth scaling, and local anesthetic injections.…”
Section: Methodsmentioning
confidence: 99%
“…Each question has five response alternatives, from 'not anxious' to 'extremely anxious', yielding a range of 5-25 for the total score, with a higher score representing higher dental fear. The MDAS scores were classified into two categories: high dental fear (MDAS scores [19][20][21][22][23][24][25] and no-to moderate dental fear (MDAS scores 5-18), according to HUMPH-RIS et al (22,24).…”
Section: Questionnairesmentioning
confidence: 99%